2003
DOI: 10.1002/cncr.11422
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma with retroperitoneal lymph nodes

Abstract: BACKGROUNDThe current study was performed to determine the impact of the presence of retroperitoneal lymphadenopathy on the survival and response to immunotherapy of patients with metastatic renal cell carcinoma (RCC).METHODSA retrospective cohort study was performed with outcome assessment based on the chart review of demographic, clinical, and pathologic data from 1087 patients. Patients with RCC who did not present with metastatic disease, who did not undergo nephrectomy as part of their cancer treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(25 citation statements)
references
References 56 publications
0
22
0
3
Order By: Relevance
“…Pantuck et al [7] at the UCLA showed the impact of lymph node-positive disease on a large cohort of metastatic patients (322 M1 patients) treated with nephrectomy. In this study, 236 patients with pathologic N0M1 RCC were compared with 86 patients with pathologic NþM1, and outcomes following systemic immunotherapy were analyzed.…”
Section: Current Practice and Evidence-based Examination By Patient Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Pantuck et al [7] at the UCLA showed the impact of lymph node-positive disease on a large cohort of metastatic patients (322 M1 patients) treated with nephrectomy. In this study, 236 patients with pathologic N0M1 RCC were compared with 86 patients with pathologic NþM1, and outcomes following systemic immunotherapy were analyzed.…”
Section: Current Practice and Evidence-based Examination By Patient Cmentioning
confidence: 99%
“…The 5-year survival of patients with lymph node-only metastasis ranges from 5 to 40% [3,7,[18][19][20]. Prospective assessment of a patient's risk of occult lymph node metastasis would assist surgeons in planning for lymphadenectomy and at the very least improve staging over omitting lymphadenectomy [19,20].…”
Section: Preoperative Nomograms/protocols For Lymph Node Dissectionmentioning
confidence: 99%
“…Pantuck et al [10] fan den bei 2 von 385 Pa ti enten ohne Lymph kno ten dis sek ti on im weidig lich bei 3 der Fäl le wer den bei CT-nega ti vem Lymph kno tens ta ging in der histo lo gi schen Un ter su chung Me tas ta sen gefun den [2,9]. Um ge kehrt er wei sen sich im CT auf fäl li ge Lymph kno ten in bis zu 58 als falsch-po si ti ve Be fun de [14].…”
Section: Prog Nos Ti Sche Ein Schät Zungunclassified
“…Die 5-Jah res-Über lebens ra ten be tra gen für pN0-Pa ti en ten ca. 75, die der pN+-Pa ti en ten 20 [10].…”
Section: Ent Steht Ein the Ra Peu Ti Scher Nut Zen Durch Die Ent Fer unclassified
See 1 more Smart Citation